La doctrina del Control de Convencionalidad. Un pretendido cambio de paradigma en la región americana - Tello Mendoza, Juan Alonso (2019)
This article has three purposes in order to contribute to the ongoing debate around the doctrine of conventionality control. First, to determine its current definition according to the own jurisprudence of the Inter-American Court of Human Rights. Secondly, to present the most relevant consequences that, both in constitutional law and in public international law, suppose the acceptance of this doctrine in question. In the third place, we intend to show why the eventual States’ approval of this doctrine must take into account, preferably, the parliament participation rather than the national high courts’ involvement.